DESIGN OF AN UXILIARY FURNITURE FOR PATIENTS IN REHABILITATION STAGE - Ntintakis, Ioannis; Ferfyri, Sotiria (Innovation in Woodworking Industry and Engineering design, 2019)
Human spin is a complicate and sensitive body part. Every spine is as unique as a fingerprint. Every person has his own unique ‘spine print’, and that print changes as the person’s posture changes. Injuries in the spine can cause serious problems in a person’s daily life. Sometimes the conservative treatment that is often applied is not enough, so surgical intervention is necessary. A serious kind of spine surgery is spinal fusion which is a surgical procedure used to correct problems with small bones in the spine (vertebrae). It is essentially a "welding" process. After this stage, the patient is undergoing rehabilitation, a stage that varies from person to person. The rehabilitation stage is temporary and it is very critical for patient’s recovery. During this phase the patient have to follow doctor guidelines in a very restrict program. In current research, auxiliary furniture is designed, aimed to improving the quality of people life in rehabilitation stage after a serious surgery of spinal fusion.